Black Agates from Paleoproterozoic Pillow Lavas (Onega Basin, Karelian Craton, NW Russia): Mineralogy and Proposed Origin - Evgeniya N. Svetova; Svetlana Y. Chazhengina; Alexandra V. Stepanova; Sergei A. Svetov (Minerals, 2021)
The present study provides the first detailed investigation of black agates occurring in volcanic rocks of the Zaonega Formation within the Onega Basin (Karelian Craton, Fennoscandian Shield). Three characteristic texture types of black agates were identified: monocentric concentrically zoning agates, polycentric spherulitic agates, and moss agates. The silica matrix of black agates is only composed of length-fast and zebraic chalcedony, micro- and macro-crystalline quartz, and quartzine. In addition to silica minerals, calcite, chlorite, feldspar, sulphides, and carbonaceous matter were also recognised. The black colour of agates is related to the presence of disseminated carbonaceous matter (CM) with a bulk content of less than 1 wt.%. Raman spectroscopy revealed that CM from black agates might be attributed to poorly ordered CM. The metamorphic temperature for CM from moss and spherulitic agates was determined to be close to 330 °C, whereas CM from concentrically zoning agates is characterised by a lower temperature, 264 °C. The potential source of CM in moss and spherulitic agates is associated with the hydrothermal fluids enriched in CM incorporated from underlaying carbon-bearing shungite rocks. The concentrically zoning agates contained heterogeneous CM originated both from the inter-pillow matrix and/or hydrothermal fluids.